PROBLEMS OF HR MANAGEMENT AND INFORMAL EMPLOYMENT IN MODERN INDUSTRIES - Mustafayev Amirjon; Boymurodov Janon (Ecominds Press, 2025)
This article discusses human resource management and its prospects, modern HR management practices, as well as employee recruitment and legal administration, staff development and training, and the significance of digital technologies and artificial intelligence in socio-economic life.
Keywords: Human resource management, recruitment, motivation, competencies, remote work, talent management, public and private sectors.